Dealing with post-excavation data: the Omeka S TiMMA web-database - Rueff, Bastien (Peer Community Journal)

(untitled)
This paper reports on the creation and use of a web database designed as part of the TiMMA project with the Content Management System Omeka S. Rather than resulting in a technical manual, its goal is to analyze the relevance of using Omeka S in the frame of a post-excavation project, gathering a wide team of researchers from several countries, working in their own language and having their own specialty. Designed to assist organizations and institutions in creating and managing digital collections, Omeka S offers a number of commodities from the perspective of both the administrator(s) and the users, the most significant being its efficiency in capitalizing on linked data standards for items description. Additionally, one of the successful achievements of this platform is to benefit the open-science tools more broadly, permitting for instance, as was done in this project, to import images with the iiiF API and bibliographical references with the Zotero module, thus avoiding the creation of new digital files and metadata. Designed with simplicity in mind, the graphic interface of Omeka S makes it a particularly appropriate tool for collective projects, permitting each user to perform a specific role and record data in their chosen language. This user-friendliness extends up to the data recording and publishing, as well as to the website designing which requires no specific skills in code. The TiMMA project also faces the limitations of Omeka S, such as the lack of efficiency of the search engine, which makes the use of web-semantic vocabularies difficult, a few bugs, and the absence of convenient functionalities in archaeological projects (e.g. the automatic creation of primary keys, a statistic dashboard, cells’ automatic filling). Despite these limitations, the TiMMA project contributes to showing that, without being a complete archaeological system recording, Omeka S is adapted to post-excavation projects.